1988
DOI: 10.1007/bf00698664
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxygen concentration on embryonic development in rats: a light and electron microscopic study using whole-embryo culture techniques

Abstract: By using a whole-embryo culture technique (New 1978), the effects of oxygen concentration (5%, 20% and 95% oxygen) on embryonic development in the rat were investigated by light and electron microscopy. The best embryonic development occurred when the 9.5-day-old embryos were cultured for 24 h with 5% oxygen, and the 10.5-day-old embryos with 20% oxygen (optimum oxygen concentration). When the 9.5- and 10.5-day-old embryos were cultured for 24 h with too little or too much oxygen, retardation of the embryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Cultures were gassed 3 times, the first gas phase lasting 18 h (5% O 2 , 5% CO 2 and 90% N 2 ), the second phase until hour 26 (20% O 2 , 5% CO 2 and 75% N 2 ), and the third phase for the remainder of the 48-hour incubation period (40% O 2 , 5% CO 2 and 55% N 2 ). The progressive gas phase changes are necessary to avoid initial oxygen toxicity and allow optimal growth in later stages [New et al, 1976;Miki et al, 1988].…”
Section: Methodsmentioning
confidence: 99%
“…Cultures were gassed 3 times, the first gas phase lasting 18 h (5% O 2 , 5% CO 2 and 90% N 2 ), the second phase until hour 26 (20% O 2 , 5% CO 2 and 75% N 2 ), and the third phase for the remainder of the 48-hour incubation period (40% O 2 , 5% CO 2 and 55% N 2 ). The progressive gas phase changes are necessary to avoid initial oxygen toxicity and allow optimal growth in later stages [New et al, 1976;Miki et al, 1988].…”
Section: Methodsmentioning
confidence: 99%
“…Other factors may be related to the handling of the blastocysts before grafting. It is well known, for example, that successful cultivation of mammalian embryos depends on the correct oxygen concentration [Morriss and New, 1979;Miki et al, 1988]. Optimal implantation sites and oxygen concentrations will be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Osmoregulatory disturbances and hypervolemia produced by moderate hypoxia resulted in abnormal development [9]. Miki et al [12] demonstrated that hypoxic conditions in cultured rat embryos caused retardation of embryonic growth and abnormal development, and the changes were due to cellular degeneration and necrosis in the neural tube, the somites and the mesenchyme. The yolk sac in culture is mainly responsible for the nutrition of cultured embryos [6,7].…”
Section: Discussionmentioning
confidence: 99%